The Effectiveness of the Student Facilitator and Explaining Learning Model Assisted by Ular Tangga Panah Media on Akidah Akhlak Learning Outcomes - Faizah, Silviana; Ummu Khairiyah; Farah Destria Rifanah; Mamlu’atur Rohmah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This study aims to assess how well the Student Facilitator and Explaining (SFE) learning model, in conjunction with the ular tangga panah media, can enhance the learning outcomes of third-grade students in the Akidah Akhlak course. A quasi-experimental nonequivalent pretest-posttest control group design was employed, involving an experimental group (SFE learning model) and a control group (Numbered Heads Together/NHT), with 52 students participating. Pretests and posttests were used as data collection methods for both groups, and the data were analyzed using an independent sample t-test. The results showed a significant difference in the average posttest scores between the experimental group (M=82.47) and the control group (M=76.36), with a significance value of 0.021, indicating that the SFE learning model was more effective in improving Akidah Akhlak learning outcomes. The novelty of this research lies in implementing an interactive and engaging learning paradigm enhanced with competitive and game-like features. This study presents an alternative learning strategy that improves student learning outcomes in the context of Akidah Akhlak subjects while also fostering interest and collaboration skills.